Tiešās metodes skolēnu runātprasmes attīstībai 6.klasē - Circene, Jeļena (Latvijas Universitāte, 2008)
Speaking skill is regarded to be one of the basic measures of knowing a language, and foreign language learners often find speaking as the most important skill they can acquire in foreign language learning. The task of English language teacher is to develop speaking skills of the students using different methods. The aim of the Diploma Paper is to explore the use of Direct Methods in developing speaking skills in basic school. The present research is conducted on the basis of a case study, which examines a case of developing speaking skills through Direct Methods in Kursishi Basic School in the period from September until October 2008. The sample of the research is ten 12 – 14 years old learners of the sixth form whose English proficiency level is elementary. The research data are collected by means of a pedagogical observation, applying questionnaires for the learners who took part in the case study, and the test of Direct Methods in order to measure the improvement of students’ speaking skills. The results of the research prove that speaking skills should be regarded as central to foreign language learning. Direct Methods are one of the most effective methods that facilitate the language learners’ communicative competence and provide students the opportunity to start speaking a foreign language at the very beginning of the learning process. Direct Methods help students to produce spoken language with ease, speak with good command of intonation, vocabulary and grammar, communicate ideas effectively and produce speech without causing comprehension difficulties. Therefore, Direct Methods of teaching English and developing speaking skills should be incorporated into the methods of teaching English language in basic school.

Runātprasme tiek uzskatīta par vienu no tām prasmēm, pēc kuras tiek izvērtētas svešvalodas zināšanas. Tie, kas mācās svešvalodu, parasti uzskata runātprasmi par vienu no svarīgākajām valodas prasmēm. Angļu valodas skolotāja uzdevums ir ar dažādu metožu palīdzību attīstīt skolēnu runātprasmi. Diplomdarba mērķis ir izvērtēt tiešo metožu pielietojumu, attīstot runātprasmi pamatskolā. Pētījums iepazīstina ar mācību pamatiem, kas tika izvērtēti, attīstot runātprasmi, izmantojot tiešās metodes, Saldus rajona Kursīšu pamatskolā laika periodā no 2008. gada septembra līdz oktobrim. Pētījuma izlasi veido desmit 12 – 14 gadus veci skolēni, kuru angļu valodas apguves prasme ir iesācēju līmenī. Pētījuma dati tika iegūti un apkopoti vecot pedagoģiskos novērojumus, izmantojot pētījuma dalībnieku anketēšanu par tiešo metožu pielietojumu valodas runātprasmju uzlabošanā, kā arī ar tiešo metožu testa palīdzību, lai izvērtētu skolēnu runāšanas prasmes attīstības dinamiku. Pētījuma rezultātā tika pierādīts, ka runāšanas prasme ir viena no svarīgākām prasmēm svešvalodu apguvē. Tiešām metodēm ir efektīvi paņēmieni, kas attīta skolēnu komunikatīvo kompetenci, un piedāvā skolēniem iespēju sākt runāt svešvalodā uzreiz, tekoši, ar vieglumu, labu intonāciju, vārdu krājumu, gramatiku, kā arī tās rada pastāvīgas sarunas un par sevi pārliecības izjūtu. Tāpēc, tiešās metodes ir jāiekļauj skolotāja darbā, mācot angļu valodu pamatskolā.
Direct Methods in Developing Students' Speaking Skills in Form 6
Keywords: Pedagoģija